Cooperation beyond group boundaries is evaluated differently depending on the existence of intergroup competition - Tateishi, Wakaba; Takahashi, Nobuyuki (Frontiers in Behavioral Economics, 2025)
Do reputational mechanisms hinder or promote cooperation beyond group boundaries? This study explores the possibility that individuals lose reputational benefits within their group when they cooperate beyond group boundaries. We examined the evaluations of those who cooperated only with ingroup members (i.e., ingroup favoring strategy) and those who cooperated with both ingroup and outgroup members (i.e., universalistic strategy) by manipulating the existence of intergroup competition through an incentivized behavioral experiment. The results show that individuals' reputations were evaluated differently depending on conditions. In the competitive condition, the ingroup favoring strategy was evaluated more positively than the universalistic strategy. In the non-competitive condition, the universalistic strategy was evaluated as positively as the ingroup favoring strategy. The reputational dynamics of indirect reciprocity are less likely to promote cooperation beyond group boundaries, particularly in the existence of intergroup competition.